Quantitative Analysis of Bioactive Compounds in Extract and Fraction of Star Fruit (Averrhoa carambola L.) Leaves using High Performance Liquid Chromatography - Yunarto, Nanang; Sulistyaningrum, Novi (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2017)
Star fruit (Averrhoa carambola L.) is potential as raw material for medicine, native in tropic areas, including Indonesia. According to other study report, star fruit leaves containing flavonoids apigenin and quercetin as potential anti-inflammatory and anticancer agents. The raw material for the drug in Indonesia mostly obtained through imports from other countries. In order to support the independence of traditional medicine raw materials, it is important to standardize the quality of traditional medicine raw materials, in this case is star fruit leaves by High Performance Liquid Chromatography (HPLC) method. The sample used is star fruit leaves extract obtained from maceration process using ethanol 70%; water fraction, ethyl acetate and hexane fractions obtained from fractionation process of the ethanolic extract. Physical parameters analyzed in sample include appearance, color, odor, taste, extract yield, water content, loss of drying, total ash content, residual solvent. Chemical parameters analyzed include apigenin and quercetin contents. The results shows that star fruit leaves used in this study meet the standards of Indonesian Herbal Pharmacopoeia with highest apigenin (6.37%) and quercetin (4.49%) content are in ethyl acetate fraction.